Increased Risk of Dementia in Patients With Systemic Lupus Erythematosus: A Nationwide Population‐Based Cohort Study. Issue 12 (28th November 2016) - Lin, Yu‐Ru; Chou, Lin‐Chuan; Chen, Hung‐Chou; Liou, Tsan‐Hon; Huang, Shih‐Wei; Lin, Hui‐Wen
Abstract : Objective: Systemic lupus erythematosus (SLE) is a systemic autoimmune disorder characterized by varied clinical symptoms and can be comorbid with neuropsychiatric disorders. However, the association between SLE and dementia risk in patients with SLE remains unclear. In this study, we evaluated the incidence of dementia in patients with SLE. Methods: Patients were recruited from a nationwide cohort in 2004–2008 and categorized as SLE (n = 1, 074; patients diagnosed with SLE) or non‐SLE (n = 5, 370; age‐ and sex‐matched controls). Each patient was followed for up to 7 years, until either receiving a diagnosis of dementia or until December 31, 2010. Data were analyzed using the Kaplan‐Meier method and Cox regression analysis. Results: The incidence rate of dementia was higher in the SLE cohort (357 per 100, 000 person‐years) than in the non‐SLE cohort (180 per 100, 000 person‐years). Patients with SLE had a higher risk of dementia than did those without SLE (crude hazard ratio [HR] 1.92; P < 0.05). Cox regression analysis revealed an adjusted HR for dementia in the SLE cohort of 2.14 ( P < 0.001), after adjustment for other comorbid diseases and variables. Conclusion: Patients with SLE have a higher risk of dementia.